1992
DOI: 10.1002/dc.2840080619
|View full text |Cite
|
Sign up to set email alerts
|

Detection of numerical chromosomal abnormalities in malignant cells on body fluids by fluorescence in situ hybridization of interphase cell nuclei with chromosome‐specific probes

Abstract: To detect numerical chromosomal abnormalities (NCA) in malignant cells on body fluids, Fluorescence in situ hybridization (FISH) technique was tested in clinical specimens from patients with metastatic disease. Directly labeled DNA probes specific for chromosomes 8, 12, X, and Y (Imagenetics, Naperville, IL) were used for in situ hybridization to interphase cell nuclei. Fifteen body fluids (BF) from various sites were studied. Based initially on the Papanicolaou-stained slides, there were seven malignant and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
(4 reference statements)
2
29
1
Order By: Relevance
“…In their study, a decrease in disomy apparently correlated well with more severe stages, indicating that along with other methods, aneuploidy analysis by FISH may be useful in determining diagnostic and prognostic parameters. In contrast to the results recently published by Cajulis and Frias-Hidvegi, 14 we did not observe a decrease in the number of signals with increasing duration of storage prior to hybridization, although more than 50% of the slides were stored for more than one year. We are wondering if this may be due to the different storage conditions the slides were kept under.…”
Section: Discussioncontrasting
confidence: 57%
“…In their study, a decrease in disomy apparently correlated well with more severe stages, indicating that along with other methods, aneuploidy analysis by FISH may be useful in determining diagnostic and prognostic parameters. In contrast to the results recently published by Cajulis and Frias-Hidvegi, 14 we did not observe a decrease in the number of signals with increasing duration of storage prior to hybridization, although more than 50% of the slides were stored for more than one year. We are wondering if this may be due to the different storage conditions the slides were kept under.…”
Section: Discussioncontrasting
confidence: 57%
“…Recently it has been proposed that polysomy may support the cytologic diagnosis of malignancy. 2 Even though this will be true in most cases, our knowledge of cytogenetic findings in nonneoplastic tissues is very limited. Recently there has been an increasing number of reports showing numerical chromosomal aberrations in normal tissues and benign tumors.…”
Section: A B Cmentioning
confidence: 99%
“…A few studies have performed FISH on cytologic specimens, but most studies are of effusions or aspirates of surgical specimens and not of FNAB specimens of lymph nodes. 2,9,10 Cytogenetic studies have shown several nonrandom alterations in patients with CLL. Abnormalities include numeric changes of chromosome 12 and deletions and/or translocations involving chromosome 13.…”
Section: Discussionmentioning
confidence: 99%